Impact of telemedicine mobile units on health outcomes, healthcare system resilience, and disaster response in flood-affected areas: a case study of Sehat Kahani - Hamna Khuld (Interdisciplinary Journal of Epidemiology and Public Health)
Introduction: The study explores the deployment of telemedicine services. Sehat Kahani introduced a two-tier telehealth model combining physical camps, mobile units, and a telehealth app to enhance healthcare accessibility and delivery in crisis.